2014
DOI: 10.1111/ijlh.12292
|View full text |Cite
|
Sign up to set email alerts
|

Body fluid cellular analysis using the Sysmex XN‐2000 automatic hematology analyzer: focusing on malignant samples

Abstract: The BF mode on the Sysmex XN could be an alternative method for the manual counts in the BF analysis with a few drawbacks. However, if a concentration of HF-BF cells is greater than the given threshold, microscopic examination should be subsequently performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
59
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 16 publications
(46 reference statements)
6
59
0
2
Order By: Relevance
“…[15] The cell classification by instrumental method and manual staining microscopy method had a high correlation, PMN% was similar to MN%, both were 0.90, respectively. This finding was consistent with the report of Cho et al, [7] but slightly weaker than what was reported by Fleming et al The main reason for this was that the testing specimens had a high proportion of peritoneal dialysis fluid, and the test was not focused on malignant effusions, which resulted in a great improvement in the correctness of the instrument. The cut-off values of HFC% and HFC# were 4.4% and 24.5/μL, respectively, whereas the values for AUC and sensitivity and specificity were 0.707, 0.792, 0.558 and 0.708, 0.753, 0.550, respectively, which were slightly lower than what was reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…[15] The cell classification by instrumental method and manual staining microscopy method had a high correlation, PMN% was similar to MN%, both were 0.90, respectively. This finding was consistent with the report of Cho et al, [7] but slightly weaker than what was reported by Fleming et al The main reason for this was that the testing specimens had a high proportion of peritoneal dialysis fluid, and the test was not focused on malignant effusions, which resulted in a great improvement in the correctness of the instrument. The cut-off values of HFC% and HFC# were 4.4% and 24.5/μL, respectively, whereas the values for AUC and sensitivity and specificity were 0.707, 0.792, 0.558 and 0.708, 0.753, 0.550, respectively, which were slightly lower than what was reported in the literature.…”
Section: Discussionsupporting
confidence: 91%
“…The correlation coefficients of RBC and NUC were 0.99 and 0.98, respectively, which were consistent with the reported literature. [5,7] XN-1000 hematology analyzer body fluid mode is capable of classifying and counting nucleated cells, including neutrophils, lymphocytes, monocytes, eosinophils, and HFC. The neutrophils, eosinophils, and basophils were classified as polymorphocytes (PMN), and lymphocytes, macrophages, mesothelial cells, and malignant cells were classified as monocytes (MN).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, a simple, fast and inexpensive test like the total nucleated cell count and differentiation can be of great help in providing clinicians with useful diagnostic information on CNS conditions [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%